Strategi Pembelajaran Pendidikan Agama Islampada Sekolah Dasar Unggulan Daar El DzikirBulu SukoharjoTahun 2016 - , Jumanto; , Dr. Abdullah Aly, M. Ag; , Dr. M. Muhtarom, S.H, M.H (2016)
This study aims to describe how the implementation of Islamic education learning strategies and describe how the factors supporting and hindering the implementation of learning strategies Islamic religious education in elementary schools, Daar El DzikirBulu Sukoharjo. The method used to obtain data using qualitative methods with data collection techniques such as interviews were validated by observation, and documentation. The results obtained from this study is the implementation of Islamic religious education instructional strategy at SDU Daar El Dzikir in accordance with its intended purpose and in achieving the goal of all teachers prepare learning administration, prepare lesson plans and implement learning strategies quantum active learning and learning. Active learning instructional strategies used include: active knowledge sharing, information search, the power of two, jigsaw learning, study questions have. Factors supporting and hindering the implementation of Islamic education learning strategies atSDU Daar El Dzikir. Supporting factors include the application of active learning instructional strategies in learning Islamic education, facilities and adequate learning media, religious condition of religious teachers, as well as learning systems which apply a different class models between boys and girls. Inhibiting factors include lack of awareness of students to practice the teachings of Islamic education in daily life - day and the lack of time required Islamic religious education teachers to develop their potential or professionalism, both within the school and outside the school environment.